Differences in Dietary Patterns of Secondary School Students by Demographic and Lifestyle Characteristics - Woźniak Weronika; Gajda Robert; Kamińska Klaudia; Nowak Marek (Visegrad Journal on Bioeconomy and Sustainable Development, 2025)
Dietary patterns represent a set of many distinctive, jointly occurring characteristics that describe a diet that shows a relationship to health. They are subject to change and show a relationship with the socio-economic situation and lifestyle. The aim of the study was to assess the variation in dietary patterns of secondary school students from Wroclaw due to their demographic and lifestyle characteristics. A cross-sectional study using a survey questionnaire was conducted in June 2022 among 262 high school students from Wroclaw. The FFS scale, which was adapted from the KomPAN questionnaire, was used to assess the frequency of consumption of 32 food groups. Demographic characteristics were assessed using questions about gender, age, place of residence, type of school and school division number. Lifestyle characteristics asked about physical activity, time spent in front of media devices, time spent sleeping, frequency of bathing and brushing teeth, and smoking and alcohol consumption. Based on the frequency of food consumption, 3 dietary patterns were identified. The Chi2 test was used to assess the significance of differences between variables. The study group was characterized by “prudent,” “imprudent” and “junk” dietary patterns. Male gender and attendance at a technical school exacerbated the occurrence of “imprudent” and ”junk” dietary patterns. Female gender and lyceum attendance exacerbated the occurrence of ”prudent” dietary patterns. Other demographic characteristics did not impact differentiation of the identified dietary patterns. Too little or too much sleep, alcohol consumption and smoking exacerbated the incidence of “imprudent” and “junk” dietary patterns. Other lifestyle characteristics did not impact differentiation of the identified dietary patterns. Further research on assessing the relationship between dietary patterns and demographic characteristics and lifestyles of schoolchildren will increase knowledge about it and allow it to be included in the educational and intervention programs being developed.